Functional and thematic diversity of essayistics (on the example if J.Brodsky prose) (Proceedings of Southern Federal University. Philology, 2015)
The article analyzes how the classification of essay types is related to the genre forming features of essays. It is considered in what way at the end of XX - the beginning of the XXI century it has changed the understanding genre forming features of essays and its place in the literary process. Attention is paid to the genre of the essay universal signs, the importance of which is recognized by the majority of researchers: subjective and complex nature of the genre and “discontinuity” works of the genre. It also discusses the different types of genre classification of the essay, based on the features of the hermeneutic, communicative and tribal nature of the essay. According to the author in the construction of productive varieties of the genre classification can be an approach that takes into account the complex nature of literary essays and specificity of subjectivity associated with the position of the media statements in the work. On the example of prose works, J. Brodsky demonstrated relation with the theme of the work, genre features are highlighted in the main types of essays of the poet. The main variety of works of this author are biographical and autobiographical essay; sustainable variant is essay-journey. Subjectivity and leitmotif organization of the text in these works are the main markers of essayism.Keywords: essay genre, genre variety, signs of the genre, subjectivity, art essays, autobiographical essays, biographical essays.Maslakov Anton Alexandrovich - Southern Federal University, Institute of linguistics, journalism and cross-cultural communication, Russian language for foreigners dpt., lecturer. E-mail: maslakovaa@mail.ru